Barcoding and border biosecurity: identifying cyprinid fishes in the aquarium trade. - Rupert A Collins (Public Library of Science (PLoS), 2012)
Background Poorly regulated international trade in ornamental fishes poses risks to both biodiversity and economic activity via invasive alien species and exotic pathogens. Border security officials need robust tools to confirm identifications, often requiring hard-to-obtain taxonomic literature and expertise. DNA barcoding offers a potentially attractive tool for quarantine inspection, but has yet to be scrutinised for aquarium fishes. Here, we present a barcoding approach for ornamental cyprinid fishes by: (1) expanding current barcode reference libraries; (2) assessing barcode congruence with morphological identifications under numerous scenarios (e.g. inclusion of GenBank data, presence of singleton species, choice of analytical method); and (3) providing supplementary information to identify difficult species. Methodology/principal findings We sampled 172 ornamental cyprinid fish species from the international trade, and provide data for 91 species currently unrepresented in reference libraries (GenBank/Bold). DNA barcodes were found to be highly congruent with our morphological assignments, achieving success rates of 90-99%, depending on the method used (neighbour-joining monophyly, bootstrap, nearest neighbour, GMYC, percent threshold). Inclusion of data from GenBank (additional 157 spp.) resulted in a more comprehensive library, but at a cost to success rate due to the increased number of singleton species. In addition to DNA barcodes, our study also provides supporting data in the form of specimen images, morphological characters, taxonomic bibliography, preserved vouchers, and nuclear rhodopsin sequences. Using this nuclear rhodopsin data we also uncovered evidence of interspecific hybridisation, and highlighted unrecognised diversity within popular aquarium species, including the endangered Indian barb Puntius denisonii. Conclusions/significance We demonstrate that DNA barcoding provides a highly effective biosecurity tool for rapidly identifying ornamental fishes. In cases where DNA barcodes are unable to offer an identification, we improve on previous studies by consolidating supplementary information from multiple data sources, and empower biosecurity agencies to confidently identify high-risk fishes in the aquarium trade.